2013
DOI: 10.1126/science.1237439
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Stability of the Human Gut Microbiota

Abstract: A low-error 16S rRNA amplicon sequencing method (LEA-Seq) plus whole genome sequencing of >500 cultured isolates were used to characterize bacterial strain composition in the fecal microbiota of 37 USA adults sampled for up to five years. Microbiota stability follows a power law function which, when extrapolated, suggests that most strains in an individual are residents for decades. Shared strains were recovered from family members, but not from unrelated individuals. Sampling individuals for up to 32 weeks wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

90
1,415
6
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,797 publications
(1,532 citation statements)
references
References 40 publications
90
1,415
6
21
Order By: Relevance
“…All omic levels exhibited individuality and family specificity, which has previously been described only for metagenomes [3][4][5] . The observed individual patterns in relation to secreted human proteins may well be an important factor shaping the gastrointestinal microbiome, culminating in the observed individuality.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…All omic levels exhibited individuality and family specificity, which has previously been described only for metagenomes [3][4][5] . The observed individual patterns in relation to secreted human proteins may well be an important factor shaping the gastrointestinal microbiome, culminating in the observed individuality.…”
Section: Discussionmentioning
confidence: 64%
“…In addition to community stability, the persistence of individualspecific strains has been documented 4,5 . To explore whether strain specificity also translates to the functional level, we analysed the encoded functional potential and corresponding expression profiles of closely related reconstructed genomes recovered from different samples.…”
Section: Functional Individuality Of Discrete Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other systems ranging from hydra to fish and mice, closely related hosts harbor more similar microbial communities than do more distantly related individuals (Zoetendal et al, 2001;Friswell et al, 2010;Navarrete et al, 2012;Faith et al, 2013;Franzenburg et al, 2013). The ongoing discovery of particular loci that shape the gut microbiome in model organisms (Benson et al, 2010) presents an intriguing target for future studies across animal systems in both the lab and field.…”
Section: Drivers Of Natural Microbiome Compositionmentioning
confidence: 99%
“…But it is important to recognise that a major result of recent biological research is precisely that very often a physiological individual is not as such a reproducing entity, but rather a local nexus of different lineages of reproducing entities. Indeed, work on symbiosis has shown that virtually all physiological individuals are multispecies units (Pradeu and Carosella 2006;Dupré and O'Malley 2009;Bosch and McFall-Ngai 2011;Pradeu 2012), functionallyintegrated wholes that unify an extraordinarily diverse range of living constituents -in particular bacteria (Bäckhed et al 2005;Faith et al 2013), fungi (Underhill andIliev 2014), andviruses (Virgin 2014). Such a physiological whole does not include as its constituents all the microbes that are in or on the host, only those that both interact strongly with other host's constituents and make a critical contribution to the functioning and survival of the whole.…”
Section: Evolutionary Individuality and Physiological Individuality Dmentioning
confidence: 99%